Microbiota: A potential orchestrator of antidiabetic therapy - Liu, Bingyao; Zhang, Linlin; Yang, Hang; Zheng, Hongting; Liao, Xiaoyu (Frontiers in Endocrinology, 2023)
The gut microbiota, as a ‘new organ’ of humans, has been identified to affect many biological processes, including immunity, inflammatory response, gut-brain neural circuits, and energy metabolism. Profound dysbiosis of the gut microbiome could change the metabolic pattern, aggravate systemic inflammation and insulin resistance, and exacerbate metabolic disturbance and the progression of type 2 diabetes (T2D). The aim of this review is to focus on the potential roles and functional mechanisms of gut microbiota in the antidiabetic therapy. In general, antidiabetic drugs (α-glucosidase inhibitor, biguanides, incretin-based agents, and traditional Chinese medicine) induce the alteration of microbial diversity and composition, and the levels of bacterial component and derived metabolites, such as lipopolysaccharide (LPS), short chain fatty acids (SCFAs), bile acids and indoles. The altered microbial metabolites are involved in the regulation of gut barrier, inflammation response, insulin resistance and glucose homeostasis. Furthermore, we summarize the new strategies for antidiabetic treatment based on microbial regulation, such as pro/prebiotics administration and fecal microbiota transplantation, and discuss the need for more basic and clinical researches to evaluate the feasibility and efficacy of the new therapies for diabetes.